Two Hundred Gastrointestinal Stromal Tumors: Recurrence Patterns and Prognostic Factors for Survival - Dematteo, Ronald P. (Institutional Knowledge at Singapore Management University, 2000)
Objective: To analyze the outcome of 200 patients with gastrointestinal stromal tumor (GIST) who were treated at a single institution and followed up prospectively. Summary Background Data: A GIST is a visceral sarcoma that arises from the gastrointestinal tract. Surgical resection is the mainstay of treatment because adjuvant therapy is unproven. Methods: Two hundred patients with malignant GIST were admitted and treated at Memorial Hospital during the past 16 years. Patient, tumor, and treatment variables were analyzed to identify patterns of tumor recurrence and factors that predict survival. Results: Of the 200 patients, 46% had primary disease without metastasis, 47% had metastasis, and 7% had isolated local recurrence. In patients with primary disease who underwent complete resection of gross disease (n = 80), the 5-year actuarial survival rate was 54%, and survival was predicted by tumor size but not microscopic margins of resection. Recurrence of disease after resection was predominantly intraabdominal and involved the original tumor site, peritoneum, and liver. Conclusions: GISTs are uncommon sarcomas. Tumor size predicts disease-specific survival in patients with primary disease who undergo complete gross resection. Tumor recurrence tends to be intraabdominal. Investigational protocols are indicated to reduce the rate of recurrence after resection and to improve the outcome for patients with GIST.